Improving quality and performance in substance use treatment programs: What is being done and why is it so hard?. (March 2021) - Davis, Margot T; Torres, Maria; Nguyen, AnMarie; Stewart, Maureen; Reif, Sharon
Summary: As states plan to implement system-wide change of any kind, it is important to understand program directors' perspectives on challenges they face. This is especially true with quality improvement reforms. Much research has focused on quality improvement in medicine, but there is a gap in our knowledge about programs that treat individuals with drug or alcohol use. From 2007 to 2016, Maine contracted with selected substance use treatment programs using financial incentives to improve quality, with focus on treatment access, engagement, retention, and completion as measures of quality. Using surveys and in-depth interviews, this research documents strategies that programs used to improve performance and challenges faced in implementing reforms. Only programs that received federal block grant funding through the state to provide substance use treatment were eligible for an incentive contract, creating a natural experiment with non-block grant programs (non-incentive). Directors were interviewed in incentive ( n  = 13) and non-incentive programs ( n  = 12). Findings: Thematic analysis revealed that: (1) programs focused on quality improvement, incentive and non-incentive programs focused on different quality measures, (2) most of the reforms in both groups targeted improving treatment access and retention, and (3) programs faced substantial challenges in undertaking reforms. Despite efforts, many programs could not meet quality measures consistently over time and faced environmental and system barriers. Applications: Policy makers and program administrators will benefit from knowing the challenges of undertaking quality improvement initiatives and provide support for the programs.